Plant-based aquafeeds : carry-over potential of mycotoxins and phytoestrogens from feed to fish and implication for fish health and food safety - Johny, Amritha (Norwegian University of Life Sciences, Ås, 2020)
The introduction of novel feed ingredients has brought tremendous changes in the field of aquaculture. The shift to non-marine resources was necessary because of rising prices for fish meal and fish oil and their decreasing availability. At the same time, the total global as well as the per-capita fish consumption has increased, which has caused an enormous expansion of the fish farming industry. The introduction of suitable alternatives for the fish-derived feed components was therefore a pre-requisite for the growth of aquaculture. Novel feed ingredients are currently mostly plant-based, including vegetable oils and protein concentrates from different legumes or wheat gluten. The change in aquafeeds towards “green” ingredients may have negative effects on fish health and product quality, which in turn can lead to economic losses. The main concerns are connected to the presence of plant-borne contaminants including endogenous anti-nutritional factors (ANF). However, new feed processing techniques methods have considerably reduced their occurrence, and sensitive detection methods allow controlling compliance with maximum levels that have been implemented by food and feed safety authorities. Nevertheless, some ANF such as natural toxins, phytoestrogens and allergenic peptides are rather resistant to heat and digestion and have the potential to be carried over into the food chain. The biological activities of these substances in fish is little known and requires more detailed investigation. This thesis addresses the impact of “green” aquafeeds on fish health and food safety, focussing on mycotoxins and phytoestrogens that are typically present in plant-based ingredients used for fish diets. The plant ingredients used in this study were wheat gluten (WG), soybean protein concentrate (SPC) and pea protein concentrate (PPC), which were fed to zebrafish (Danio rerio) and Atlantic salmon (Salmo salar L.) with the aim to investigate possible effects on the fish and the transmissibility potentials of target ANF into ...